Traceability and foreign corporate accountability in mineral supply chains - Svenja Schöneich; Christina Saulich; Melanie Müller (Regulation & Governance, 2023)
Industrialized economies in the EU depend heavily on imports of minerals. The extraction and parts of the transport and processing of these minerals take place in the Global South and often bear high human rights and environmental risks. A lack of traceability in mineral supply chains makes it particularly difficult to hold companies accountable for negative environmental and social impacts of their operations and those of their suppliers. This paper analyses three mineral supply chains (copper, platinum, and gold) in order to develop propositions about how supply chain-specific characteristics affect traceability and foreign corporate accountability (FCA) in mineral supply chains. The analytical framework focuses on three dimensions: geopolitical dynamics, industry characteristics, and private governance mechanisms. The authors argue that chain-specific characteristics may foster or thwart traceability and FCA in mineral supply chains and thus provides a novel contribution to the debate on traceability and accountability in mineral supply chains.
Keywords: 330; copper; gold; mineral supply chains; platinum; traceability